Antigenotoxic potential of the aqueous basidiocarp extracts of Calocybe indica - Deepthi, A. S.; Joseph, Nisha; Annakutty, A. G. (Current Botany, 2024)
Calocybe indica, commonly known as the milky white mushroom, is an edible mushroom native to India. The antigenotoxic potential of the aqueous basidiocarp extract (25 g/L and 50 g/L) of C. indica was investigated using the Allium cepa test system. Meristematic cells of root tips treated with 100% Coca-Cola served as a positive control. A significant reduction in the mitotic index (7.83 ± 0.60) was observed in the positive control (100% Coca-Cola) compared to the negative control. The highest percentage (65.25 ± 4.58) of chromosomal abnormalities was observed in the positive control. Chromosomal abnormalities were significantly reduced in root tip cells treated with Coca-Cola followed by treatment with basidiocarp extracts such as 25 g/L and 50 g/L (30.32 ± 4.44 and 14.20 ± 2.41, respectively). Coca-Cola induced chromosomal abnormalities were reduced by treatment with basidiocarp extracts, demonstrating the antimutagenic potential of C. indica. The present study indicates that the aqueous basidiocarp extracts of C. indica have anti-genotoxic effects. The clastogenic abnormalities caused by Coca-Cola are competently restored in the root meristem cells of A. cepa treated with the extract.